A step by step approach in differential diagnosing of adrenal incidentaloma (epinephroma), (with comments on the new Clinical Practice Guidelines of the European Society of Endocrinology) - Farrugia Frederick-Anthony; Misiakos Evangelos; Martikos Georgios; Tzanetis Panagiotis; Charalampopoulos Anestis; Zavras Nicolaos; Sotiropoulos Dimitrios; Koliakos Nikolaos (Sciendo, 2017)
Objectives. To present a step by step approach for the diagnosis of adrenal incidentaloma (AI).